SUBSTANCE OF TRANSFORMATIONAL PROCESSES IN ECONOMIC SYSTEMS - Барановський , Олександр (Socio-economic relations in the digital society, 2019)
Critically analyzed the evolution and the status of the research and approaches of scientists to definition of the substance of the transformation and transformational processes. Logically non-completed provisions of theory of economic transformation are stressed. Specifics of renewable, process (radical process an evolutional process), formational, civilizational, dialectic, situational, management, institutional, elements, system, level, functional, informational approaches to understanding of nature of transformation is described. Attention is stressed on differences in treatment of the transformation in transformational theory of financial agents, theories of economic transformation, institutional turn, civil order; ordoliberal school of neoinstitutionalism. Author’s view on subject focus of researches of transformational processes in economic systems is presented. Researches on adaptation problems of different entities to transformational changes are reviewed. Components and stages of transformational processes are described. Stressed on creation during transformational processes of transformational cross, field of transformational instability, transformational transition. Interpretation of economic transformation and transformation of economic system is presented. Principles of transformation of economic systems are presented.